Towards a literary public sphere: the Mercurio Peruano, Lima, 1791 - Sharman, Adam (Taylor & Francis, 2017)
This article examines the applicability of Habermas’ concept of the public sphere to the periodical paper the Mercurio Peruano in 1791. It compares the conditions of production of Habermas’ ‘model’ eighteenth-century European bourgeois public sphere to those of a colonial, ancien régime Lima complete with Inquisition censorship. It suggests that Habermas’ literary—rather than political—public sphere, training ground for a critical civic public reflection, is the more fruitful concept. Moving beyond contextualist explanations, it argues that the Mercurio’s Enlightenment meditations on the capital’s ‘civil system’—on its commerce and its cafés—construct the public sphere through and in the productive force of critical reason itself. In its patriotic pages we glimpse both the signs of a ‘modern’ public sphere of civil society in the interstices of formal politics before independence and a reminder that the public sphere, based on a reason that exceeds any determinate historical structure, is never exclusively modern.